Taxation and agency conflicts between firm owners and managers: a review - Thomas Bauer; Thomas Kourouxous; Peter Krenn (Business Research, 2018)
When analyzing the influence of taxation on agency conflicts between firm owners and managers, one can draw on theoretical principal-agent literature from various research fields. In recent years, this interdisciplinary research has grown significantly covering research with regards to optimal compensation, investment decisions, tax avoidance and transfer pricing while analyzing the effects of corporate income taxes, wage taxes, bonus taxes and shareholder taxes. Our paper provides a comprehensive review of analytical literature that studies the influence of taxation on agency conflicts between firm owners and managers. Above and beyond summarizing research findings, we discuss how taxes are commonly implemented in agency models, derive empirical predictions, and identify research gaps for future tax research.
Keywords: 650; Analytical tax research; Principal-agent conflict; Corporate income tax; Wage tax; Bonus tax; Shareholder tax